Peran Kolaborasi dan Inovasi pada Pengembangan Ekosistem Bisnis Digital - Achmad Solechan; Ahmad Hafiyyan Shibghattalloh; Arisanti Ayu Wardhani; Hasan Aminda Syafrudin; Lubertus Wahyu Priyo Dwiantoro; Sherly Arwinda (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study examines the roles of collaboration and innovation in developing digital business ecosystems. It employs a narrative literature review of core scholarship on business ecosystems, digital platforms, and collaboration–innovation practices in both global and Indonesian contexts. The synthesis indicates that digital business ecosystems constitute multilateral interdependence structures that require alignment of roles and activities across actors to realize a shared value proposition. Collaboration therefore becomes a structural necessity, as ecosystem innovation is modular and complementary, and value emerges only when contributions from diverse parties are coherently integrated. Digital platforms accelerate ecosystem growth through generativity and network effects, yet they also demand collaborative governance to keep collective innovation coordinated and goal-oriented. Empirical evidence further shows that collaboration facilitated by platforms, hubs, or intermediaries speeds up the exchange of data, knowledge, and resources, triggering technological, service, governance, and business-model innovations that enhance ecosystem performance and sustainability. However, many ecosystems still face limitations in the depth of collaboration—often not progressing to co-production or joint R&D—resulting in suboptimal collective innovation. This study enriches digital ecosystem theory and offers practical implications for orchestrating collaboration and sustaining innovation in digital business ecosystems.